Ракообразные водоемов полярных пустынь архипелага Новая Земля - Вехов, Н.В. (Вестник зоологии, 2000)
Фауна ракообразных водоемов полярных пустынь Новой Земли автохтонная, смешанная, крайне обедненная и включает в себя всего 27 видов c преобладанием циклопов, харпактицидов и остракодов; очень мало Daphniiformes и Calanoida. Преобладают виды с космополитными ареалами, широко распространенные в Евразии, и циркумполярные. Узкоареальный вид только один (Candona sibirica). Фауна ракообразных полярных пустынь Новой Земли значительно богаче таковой островов западной части евразийской Арктики (архипелага Свальбард и о. Медвежий), причем она обогащается по мере увеличения возраста водоемов. Минимальное разнообразие характерно для водоемов приморских террас и современных морен, а максимальное для озер и мелководных биотопов на морских террасах. В работе обсуждаются также вопросы миграций видов с материка на острова. For polar deserts of the Novaya Zemlya Archipelago crustacean fauna is autochtonous, mixed, very poor and consist only 27 species. Cyclopoids, harpacticoids and octracods are predominated by species diversity; Anostraca, Daphniiformes and Calanoida are represented by 1—2 species. For discussed region, all species of crustaceans have very wast areas, i. e. cosmopolitan, widely distribution in Eurasia and circumpolare. Ostracod Candona sibirica is only species of crustaceans to have very district àreas (Novosibirskye Ostrova and Ust-Lenskii zapovednik). The crustacean fauna of polar deserts of the Novaya Zemlya Àrchipelago differ considerably by relative high diversity of species composition by comparision of western part of Eurasian Arctic (i. e. the Svalbard Archipelago, Medvezii island). In polar deserts of Novaya Zemlya the enrichment of crustacean fauna by species according to age of biotopes it have been noted. Waterbodies of maritime terraces and modern moraines are characterised by minimal diversity of crustacean fauna, but fauna of lakes and ponds in ancient marine tårraces is more richness. Problems of species migrations and formation of crustacean fauna to polar deserts are discussed.